The effects of autonomy-supportive vs. controlling guidance on learners' motivational and cognitive achievement in a structured field trip - Basten, Melanie; Meyer-Ahrens, Inga; Fries, Stefan; Wildermuth, Matthias (Science education, 2014)
Field trips can provide unique opportunities for authentic, meaningful, and self-determined learning. Capitalizing on these opportunities requires that field trips be structured. A common way to do this is through the use of educational materials such as worksheets. The extent to which the guide's or teacher's autonomy-supportive or controlling motivating style influences learning structured by worksheets has not yet been investigated. We conducted two studies focusing on this specific issue. We hypothesized that autonomy-support is beneficial to intrinsic motivation and cognitive achievement. The setting for our research involved a field trip to the local zoo. The participants were 100 fifth graders (medium achievers) for Study 1 and 106 fifth and sixth graders (high achievers) for Study 2. The classes were divided into two groups for each study. While completing worksheets, some classes were given autonomy-supportive guidance and the others controlling guidance. We assessed the pupils’ intrinsic motivation and knowledge using a pre-, post-, follow-up test design. Our research found that autonomy-support appears to be beneficial to motivation and does not seem to impair cognitive achievement. The beneficial effect of autonomy-support was found to be higher for the high-achieving pupils than for the medium achievers.
Gesehen am 04.01.2021